Evaluation of Alternatives for Dysfunctional Double Lumen Central Venous Catheters Using a Two-Compartmental Mathematical Model for Different Solutes. Issue 1 (January 2013) - Van Canneyt, Koen; Van Biesen, Wim; Vanholder, Raymond; Segers, Patrick; Verdonck, Pascal; Eloot, Sunny
Double lumen (DL) central venous catheters (CVC) often suffer from thrombosis, fibrin sheet formation, and/or suction towards the vessel wall, resulting in insufficient blood flow during hemodialysis. Reversing the catheter connection often restores blood flows, but will lead to higher recirculation. Single lumen (SL) CVCs have often fewer flow problems, but they inherently have some degree of recirculation. To assist bedside clinical decision making on optimal catheter application, we investigated mathematically the differences in dialysis adequacy using different modes of access with CVCs. A mathematical model was developed to calculate reduction ratio (RR) and total solute removal (TSR) of urea, methylguanidine (MG), beta-2-microglobulin (β2 M), and phosphate (P) during different dialysis scenarios: 4-h dialysis with a well-functioning DL CVC (DL-normal, blood flow QB 350 ml/min), dysfunctional DL CVC (DL-low flow, QB 250), reversed DL CVC (DL-reversed, QB 350, recirculation R = 10%) and 12 Fr SL CVC (effective QB 273). With DL-normal as reference, urea RR was decreased by 3.5% (DL-reversed), 13.0% (SL), and 15.6% (DL-low flow), while urea TSR was decreased by 3.3% (DL-reversed), 13.2% (SL), and 13.5% (DL-low flow). The same trend was found for MG and P. However, β2 M RR decreased only 1.5% with SL CVC although TSR decrease was 17.2%, while RR decreased 21.1% with DL-low flow although TSR decrease was only 4.9%. In the case of dysfunctional DL CVCs, reversing the catheter connection and restoring the blood flow did not impair TSR, with 10% recirculation. The SL CVC showed suboptimal TSR results that were similar to those of the dysfunctional DL CVC.